The World Commission of Science and Sports
The World Commission of Science and Sports (WCSS) is a working group of the International Council of Sports Science and Physical Education (ICSSPE). It is a non-profit making organization with the aim of promoting the application of science to sport. The WCSS was established in 1967 and is a working group for the International Council for Sports Sciences and Physical Education (ICSSPE) which is a category 'A' organization at UNESCO and a recognized organization of the IOC. Its objectives • To co-ordinate - to organise - to support - to help... in sport-specific sport science World Congresses and symposia • To encourage international co-operation in the field of sport science • To promote, stimulate and co-ordinate sport specific scientific research throughout the world and to support the application of its results in the many practical areas of sport • To make its scientific knowledge of sport and practical experiences available to all interested national and international institutions via peer-reviewed publications